(untitled) (Research, Society and Development, 2022)
The effect of magnetically treated water on the physico-chemical properties of water and soil as well as nutrient absorption during the growth of Beta vulgaris L. was evaluated in this study. The plants were either irrigated with magnetically treated water (MW), i.e., treatment group, or irrigated with common water (C), i.e., control group. The MW was obtained using a magnetic device in the range of 0.8 - 0.9 T of magnetic induction. Magnetic treatment caused a higher dissolution of salts and an increase in electrical conductivity in the water of the irrigated soil compared to common water. At the same time, the soil irrigated with MW showed a decrease in the concentrations of Ca2+ (16.6 %), K+ (9.7 %), and Na+ (13.4 %) with significant differences compared to the soil irrigated with control. However, in plants irrigated with MW, an increase in the concentration of Na+ (4.91 %) in the leaves and Fe2+ (126.3 %) in the roots was observed with significant differences compared to the control plants. In addition, several biometric parameters were significantly increased in plants irrigated with MW compared to control plants, more specifically for their fresh and dry weights of leaves (25.5 - 25.1 %) and roots (6.4 - 39.8 %), respectively. In conclusion, the magnetic treatment caused an increase in electrical conductivity in the soil and water. Consequently, an increase in the mineral absorption and the behaviour of the physiological activity in Beta vulgaris L. culture were obtained.